Remote ischemic preconditioning increases accumulated oxygen deficit in middle-distance runners - Paull, E. J.; Van Guilder, G. P. (Journal of Applied Physiology, 2019)
The mediators underlying the putative benefits of remote ischemic preconditioning (IPC) on dynamic whole body exercise performance have not been widely investigated. Our objective was to test the hypothesis that remote IPC improves supramaximal exercise performance in National Collegiate Athletic Association (NCAA) Division I middle-distance runners by increasing accumulated oxygen deficit (AOD), an indicator of glycolytic capacity. A randomized sham-controlled crossover study was employed. Ten NCAA Division I middle-distance athletes [age: 21 ± 1 yr; maximal oxygen uptake (Vo2max): 65 ± 7 ml·kg-1·min-1] completed three supramaximal running trials (baseline, after mock IPC, and with remote IPC) at 110% Vo2max to exhaustion. Remote IPC was induced in the right arm with 4 × 5 min cycles of brachial artery ischemia with 5 min of reperfusion. Supramaximal AOD (ml/kg) was calculated as the difference between the theoretical oxygen demand required for the supramaximal running bout (linear regression extrapolated from ~12 × 5 min submaximal running stages) and the actual oxygen demand for these bouts. Remote IPC [122 ± 38 s, 95% confidence interval (CI): 94-150] increased (P < 0.001) time to exhaustion 22% compared with baseline (99 ± 23 s, 95% CI: 82-116, P = 0.014) and sham (101 ± 30 s, 95% CI: 80-123, P = 0.001). In the presence of IPC, AOD was 47 ± 36 ml/kg (95% CI: 20.8-73.9), a 29% increase compared with baseline (36 ± 28 ml/kg, 95% CI: 16.3-56.9, P = 0.008) and sham (38 ± 32 ml/kg, 95% CI: 16.2-63.0, P = 0.024). Remote IPC considerably improved supramaximal exercise performance in NCAA Division I middle-distance athletes. Greater glycolytic capacity, as estimated by increased AOD, is a potential mediator for these performance improvements. NEW & NOTEWORTHY Our novel findings indicate that ischemic preconditioning enhanced glycolytic exercise capacity, enabling National Collegiate Athletic Association (NCAA) middle-distance track athletes to run ~22 s longer before exhaustion compared with baseline and mock ischemic preconditioning. The increase in "all-out" performance appears to be due to increased accumulated oxygen deficit, an index of better supramaximal capacity. Of note, enhanced exercise performance was demonstrated in a specific group of in-competition NCAA elite athletes that has already undergone substantial training of the glycolytic energy systems.